The theoretical research of an upward two-phase flow with phase’s changes in a vertical well - V. S., Shagapov; S. L., Borodin; A. A., Gubaidullin; Ngoc Hai, Duong; N. G., Musakaev (Vietnam Journal of Mechanics, 2010)
By methods of mechanics of multiphase systems the mathematical model describing an upward gas-and-oil flow in a vertical well is constructed. The model considers phase’s changes, deposition of oil paraffin on the elevating column’s walls of the well, influence of an installation of electrical centrifugal pumps on parameters of the gas-and-oil flow, and also heat exchange of the well with surrounding rock. It is shown, that at the using of an installation of electrical centrifugal pumps and variation of its metering characteristic, depth of its setting, it is possible to achieve the optimum temperature mode on all the well’s height and to prevent by it formation of paraffin deposits.